The Malaysian 'Islamic' state versus the Islamic state (IS) : evolving definitions of 'Terror' in an 'Islamising' nation-state - Chan, Nicholas Wai Yeap (2017)
This thesis is a study of the Malaysian state with regards to how it defines and redefines ' terror' as the nature of militancy changes from the period of Communist insurgency to present day's Islamist militancy. Through tracing the changes in the state's definition of a ‘terrorist’, we seek to show how the portrait of a terrorist is not only inherently political (and at certain junctures, politicised), but it also reflects on the nature of the state, as the ' terrorist' is invariably the constitutive other of the state, albeit one at the extreme end. In the case of Malaysia, we have shown that the discursive ease m externalising the ' terrorist' is not always a certainty. While the state managed to belittle and ethicise the Communist Terrorists (CTs), the rise of Islamist militancy forced the state to shelve the term ' terrorist' in favour of religious 'deviancy'. It was not until the 'war on terror' paradigm was unleashed globally after the September 11 attacks did the Malaysian state able to unfreeze the term and brazenly reintroduced it back into its political, diplomatic, and security discourse. The grappling with the definition of ' terror' also advanced parallel to a process of state-driven Islamisation where the discursive ideal that is the 'Islamic state' became a point of contention and also legitimisation. Akin to a case of semantic acrobatics, we demonstrate how the Malaysian state securitised (1980-2001), normalised (2001-2013), and resecuritised (2014 onwards) the term as a result of a balancing act which not only aimed at neutralising the elements of militancy, but also to augment the state's ' Islamic ' credentials in a bid to outplay its major Islamist opponent, the Pan Malaysian Islamic Party (PAS). At the end, following the emergence of a transnational insurgent/quasi-state/ terrorist/ideology hybrid, the Islamic State (IS), we argue that the Malaysian state is now embroiled in an ' Islamic state versus Islamic State' trap, where the state after appropriating and normalising the ' Islamic state' ideal, has no choice but to contend with what is fundamentally a ' terrorist' group (by the state's own definition) in religious terms. In the face of afar enemy which it cannot decisively eliminate, the Malaysian ' Islamic' state has no choice but to defend itself from the perspective of a nation-state, as well as Islam.